In vitro catharanthus roseus (L.) G. don callus responses to chitosan treatments - Ismail, Nur Atikah (2015)
The present study investigates the effects of chitosan on callus growth and development ofCatharanthusroseus under light treatment. In the study, chitosan was supplemented in culture medium. Callus of C. roseus, previously initiated on MS medium before the onset of the experiment was cultured. Various levels of chitosan (0, 1, 2, 3, 4, 5 mg/L) were used. The experiment was conducted in a completely randomized design with 3 replications. Study parameters include dry weight of callus andboron level. Data recorded that the control, 0 mg/L chitosan concentration gave the highest dry weight of callus 0.210 g. Treatment with 1 mg/L chitosan concentration increased boron level in callus of C. roseusto 0.097 mg/L. The study suggests that the application of chitosan in culture medium did not give significant increase in dry weight of callus compared to the control. Chitosan treatment did not give significant increase or decrease in boron level of callus. The study concludes that chitosan had no significant effect on dry weight and boron level in callus of C. roseus under light treatment.